Collective actions in the face of violence. Disquisitions based on a case study: Comuna 13 in Medellín (Colombia) - Alzate Zuluaga, Mary Luz (Frontera Norte, 2017)
This article contributes to the knowledge and visualization of the types and strategies of action that collective subjects produce to cope with violence in a context of internal armed conflict such as the kind that Colombia has experienced for over forty years. It describes them as forms of political action that attempt to reverse, transform or alter the power relations that some attempt to impose through this type of violence. At the same time, it contributes to the emergence of a new public scenario that goes beyond essentialist sovereignties, transcending the interpretations of political action from a purely state-oriented approach and a general will. Acciones colectivas frente a la violencia. Disquisiciones a partir de un estudio de caso: Comuna 13 de Medellín (Colombia) Resumen Este trabajo contribuye al conocimiento y visualización de modelos y estrategias de acción que los sujetos colectivos producen para lidiar con la violencia en un contexto de conflicto interno armado como el que Colombia ha experimentado por más de 40 años. Se les describe como formas de acción política que intentan revertir, transformar o alterar las relaciones de poder que algunos tratan de imponer por medio de este tipo de violencia. Al mismo tiempo, contribuye a la aparición de un nuevo escenario público que va más allá de las soberanías esencialistas, trascendiendo las interpretaciones de la acción política desde un enfoque únicamente orientado al Estado y a una voluntad general.